Effect of Salvia leriifolia Benth. root extracts on ischemia-reperfusion in rat skeletal muscle - Nassiri-Asl Marjan; Hosseini Azar; Hosseinzadeh Hossein; Sadeghnia Hamid-Reza (BMC, 2007)
Abstract Background Salvia leriifolia have been shown to decrease ischemia-reperfusion (I/R) injury in brain tissues. In this study, the effects of S. leriifolia aqueous and ethanolic extracts were evaluated on an animal model of I/R injury in the rat hind limb. Methods Ischemia was induced using free-flap surgery in skeletal muscle. The aqueous and ethanolic extracts of S. leriifolia (100, 200 and 400 mg/kg) root and normal saline (10 ml/kg) were administered intraperitoneally 1 h prior reperfusion. During preischemia, ischemia and reperfusion conditions the electromyographic (EMG) potentials in the muscles were recorded. The markers of oxidative stress including thiobarbituric acid reactive substances (TBARS), total sulfhydryl (SH) groups and antioxidant capacity of muscle (using FRAP assay) were measured. Results In peripheral ischemia, the average peak-to-peak amplitude during ischemic-reperfusion was found to be significantly larger in extracts groups in comparison with control group. Following extracts administration, the total SH contents and antioxidant capacity were elevated in muscle flap. The MDA level was also declined significantly in test groups. Conclusion It is concluded that S. leriifolia root extracts have some protective effects on different markers of oxidative damage in muscle tissue injury caused by lower limb ischemia-reperfusion.